Structure and Electrical Properties of Morphotropic Phase Boundary (Na1/2Bi1/2)TiO3‐PbTiO3‐Bi(Mg1/2Ti1/2)O3 Ternary System. Issue 24 (31st October 2018) - Sun, Renbing; Wang, Fang; Feng, Tangfu; Kong, Fengyu; Luo, Haosu
Abstract : The xBi(Mg0.5 Ti0.5 )O3 ‐(0.86−x)(Bi0.5 Na0.5 )TiO3 ‐0.14PbTiO3 (xBMT‐(0.86−x)NBT‐0.14PT) ( x  = 0, 0.02, 0.04, 0.06, 0.08, 0.10, 0.20) ternary solid solution ceramics are fabricated using a conventional solid‐state reaction method. The effect of tetragonality of tetragonal phase and local structure on the dielectric, ferroelectric, and piezoelectric properties is systematically investigated for the compositions near morphotropic phase boundary (MPB). The curves ϵ ( T ) for unpoled x  = 0.02, 0.04, 0.06, 0.08 samples exhibit three dielectric anomalies upon heating. With increasing the BMT content, c/a ratio of the tetragonal phase slightly decreases, and the structure turns into pseudocubic phase. The largest values of d 33 and P r are obtained for x  = 0.10 sample, being about twice as much as that of the 86NBT‐14PT sample, which can be attributed to the emergence of the nanostructure. Abstract : The effect of tetragonality of tetragonal phase and local structure on the electrical properties is studied. With increasing the Bi(Mg0.5 Ti0.5 )O3 content, c/a ratio of the tetragonal phase slightly decreases, and the structure turns into pseudocubic phase. The largest values of d 33 and P r are obtained for x  = 0.10 sample, which can be attributed to the emergence of the nanostructure.